BEHAVIOR OF MULTI-LAYER COMPOSITE CONTINUOUS BEAMS WITH PARTIAL INTERACTION - I. Aziz, Khalel (Anbar Journal of Engineering Sciences, 2008)
In this study an attempt is made to develop a method of analysis dealing with a multi-layer composite continuous beam , for linear material and shear connector behavior in which the slip (horizontal displacement) and uplift force (vertical displacement) are taken into consideration. The cross-sectional area for the beam consists of three layers varying in thickness and shear stiffness. The analysis is based on a approach presented by Roberts[1], basically for two layer simply supported beam, under uniform and point loads , which takes into consideration horizontal and vertical displacement in interfaces. The analysis led to a set of eight differential equations containing derivatives of the fourth and third order. A program based on the present analysis is built using finite difference method using boundary conditions. A comparison between the present analytical solution and previous studies shows close agreement. Continuous composite beams are very important element in construction of high rise buildings , multi-story frames and bridges, due to great advantages that can be obtained by using this sort of structural elements, such as reducing the beam moments, suitable reduction in deflections. The model deals with continuous beam consisting from three layers as a cross-sectional area with inter-layer slip. The cross-sectional area consist of composite material including intermediate layer from concrete and an upper and lower material with high strength in tension and compression ( i.e. steel plates or steel beams )